UPAYA PENINGKATAN KINERJA PELAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA MAGELANG - Siska Yuni Hartanti; Muhammad Mathori (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
The Department of Population and Civil Registration (Disdukcapil) of Magelang City is one of the public service providers that strive to provide excellent service to the community. However, the performance of public services in the Disdukcapil of Magelang City still appears various problems and complaints. The purpose of this study was to identify the public factors that caused the performance of services in the Disdukcapil of Magelang City to not meet the established standards and to formulate efforts to improve the performance of public services in the Disdukcapil of Magelang City. This type of research is descriptive with a qualitative approach. The measurement of public service performance is based on four indicators consisting of work performance, expertise, behavior, and leadership. Data were collected through observation, interview, and documentation techniques. Data analysis through the stages of data collection, data reduction, data presentation, and concluding. The results of the study can be seen that the performance of public services in the Disdukcapil of Magelang City from the aspect of achievement, expertise, behavior, and leadership has shown good results. However, in the service, there are still various problems and complaints. This is due to 2 (two) factors, namely internal factors, and external factors. The efforts to improve the performance of public services include improving the quality and behavior of government officials, creating public service policies that are not too procedural and convoluted, and adding facilities and infrastructure.